An Analysis on the Speech Act of Selena Gomez ”Trust Yourself” in English Speeches YouTube Channel - Nur Fadilah (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
The purpose of this study is to identify the various types of illocutionary act in Selena Gomez's speech "Believe in yourself". There are two main problems in this research: (1) What type the illocutionary act used by Selena Gomez in her speech on YouTube in English? (2) In Selena Gomez's speech, what illocutionary act are you most likely to see? I use a method known as content analysis. There are five types of illocutionary acts: Declaration, Representation, Expressive, Commissive, and Directive. I analyze the speech text by Selena Gomez titled "Believe in yourself." Data from Selena Gomez speeches reveal 51 examples of illocutionary behavior, these five types all illocutionary acts can be found in an utterance: representative statement; directive statement; expressive statement; commissive statement; and declaration statements. And based on this research, It can be said that the dominant illocutionary act style in speech is representative act, and the least is directive act.